Glaura y Cariolano, a neoclassical opera by Ignacio García Malo - Felipe RODRÍGUEZ MORÍN (Cuadernos Dieciochistas)
With the intention of emulating Italian operas, García Malo decided in 1791 to write one of these pieces in Spanish, in order to show that the richness and harmony of this language was comparable to that of any other foreign language, and in the hope that opera similar to Italian opera would be created in the future. Together with this patriotic intention was the aim of acclaiming Spanish splendour in America, and, through that, informing the audience of the work about the virtues of the Hispanic character, at a time in which some were worried about the future political stability of the overseas colonies. García Malo adapted the text entirely to neoclassical aesthetics, so that the message would more efficiently leave a mark on the spectator. As regards the music, composed by José Lidón, it most likely contributed to reinforcing in the listener the effect of reliving and singing the past glory of Spain.